Low Estimated GFR Predicts Hemorrhagic Complication in Acute Ischemic Stroke: A Meta-analysis - Nepal, Gaurav; Shrestha, Gentle S; Yadav, Jayant K; Pathak, Santosh; Ojha, Rajeev (Journal of Institute of Medicine Nepal, 2021)
Introduction Intracerebral hemorrhage (ICH) can occur in patients following acute ischemic stroke (AIS) and results in significant long-term morbidity and mortality. Patients with renal impairment have a higher risk of bleeding. Therefore, AIS patients with renal impairment may have a higher risk of such complications. We performed a meta-analysis of observational studies to determine the relationship between renal impairment and hemorrhagic complications in patients with AIS. Methods This meta-analysis was conducted following the guidance of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. PubMed, Google Scholar, Web of Science and CNKI were searched to identify studies published between 1995 and 2020. Relative risk estimates of all the included studies were pooled to calculate pooled OR and 95% confidence intervals. Results In our meta-analysis, 14 studies involving 10,033 AIS patients from Asia, Europe, and North America were included. We found that patients with renal impairment as indicated by low eGFR had a higher odds of developing any ICH (OR: 1.7; 95% CI: 1.13 to 2.57; p= 0.011; I2=87.2%) following AIS. Similarly, we found that patients with renal impairment had a higher odds of developing symptomatic ICH (OR: 1.7; 95% CI: 1.32 to 2.17; p= 0.000; I2=37.3%) following AIS. Conclusion Our meta-analysis found that there is an increased odds of developing any ICH and SICH in AIS patients with renal impairment.